Immune Profiling Demonstrates a Common Immune Signature of Delayed Acquired Immunodeficiency in Patients With Various Etiologies of Severe Injury*. Issue 4 (17th September 2021) - Venet, Fabienne; Textoris, Julien; Blein, Sophie; Rol, Mary-Luz; Bodinier, Maxime; Canard, Bertrand; Cortez, Pierre; Meunier, Boris; Tan, Lionel K.; Tipple, Craig; Quemeneur, Laurence; Reynier, Frédéric; et al.
Abstract : OBJECTIVES: The host response plays a central role in the pathophysiology of sepsis and severe injuries. So far, no study has comprehensively described the overtime changes of the injury-induced immune profile in a large cohort of critically ill patients with different etiologies. DESIGN: Prospective observational cohort study. SETTING: Adult ICU in a University Hospital in Lyon, France. PATIENTS: Three hundred fifty-three septic, trauma, and surgical patients and 175 healthy volunteers were included in the REAnimation Low Immune Status Marker study. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Extensive immune profiling was performed by assessing cellular phenotypes and functions, protein, and messenger RNA levels at days 1–2, 3–4, and 5–7 after inclusion using a panel of 30 standardized immune markers. Using this immunomonitoring panel, no specificity in the immune profile was observed among septic, trauma, and surgical patients. This common injury-induced immune response was characterized by an initial adaptive (i.e., physiologic) response engaging all constituents of the immune system (pro- and anti-inflammatory cytokine releases, and innate and adaptive immune responses) but not associated with increased risk of secondary infections. In contrary, the persistence in a subgroup of patients of profound immune alterations at the end of the first week after admission was associated with increased risk of secondary infections independently of exposure to invasive devices. The combined monitoring of markers of pro-/anti-inflammatory, innate, and adaptive immune responses allowed a better enrichment of patients with risk of secondary infections in the selected population. CONCLUSIONS: Using REAnimation Low Immune Status Marker immunomonitoring panel, we detected delayed injury-acquired immunodeficiency in a subgroup of severely injured patients independently of primary disease. Critically ill patients' immune status could be captured through the combined monitoring of a common panel of complementary markers of pro-/anti-inflammatory, innate, and adaptive immune responses. Such immune monitoring needs to be incorporated in larger study cohorts with more extensive immune surveillance to develop specific hypothesis allowing for identification of biological systems affecting altered immune function related to late infection in the setting of acute systemic injury.